Stockhausen 3: Elektronische musik 1952-1960 - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2001)
ETUDE Musique ConcrèteSTUDIE I and II Electronic MusicGESANG DER JÜNGLINGE / SONG OF THE YOUTHS Electronic MusicKONTAKTE / CONTACTS Electronic Music